Clinical relevance of TP53 polymorphic genetic variations in chronic lymphocytic leukemia. (July 2017) - Bilous, Nadiia; Abramenko, Iryna; Saenko, Vladimir; Chumak, Anatoliy; Dyagil, Iryna; Martina, Zoya; Kryachok, Iryna
Highlights: There are borderline associations between some TP53 SNPs and CLL risk. Pro72Pro of rs1042522 is associated with an increased incidence of TP53 mutations. Rs1800372 is associated with unfavorable prognosis of CLL. Abstract: Objectives: To analyze the distribution of single nucleotide polymorphisms (SNPs) in the TP53 gene in chronic lymphocytic leukemia (CLL) patients and to evaluate their associations with clinical behavior of the disease. Methods: SNPs in exons and parts of adjacent introns of the TP53 gene were analyzed in 235 CLL patients observed during 2005-2012 years. Data on individuals of European descent from the 1000 Genomes Project data set were used as a reference. Results: In the recessive model of inheritance, we found borderline associations between CLL risk and C/C genotype of rs1642785 (p = 0.048); G/G genotype of rs2909430 (in men only; p = 0.036) and Pro72Pro genotype of rs1042522 (in men only; p = 0.045). Risk of CLL was increased also in carriers of rare haplotypes (p = 0.0049). Besides, genotypes Pro72Pro of rs1042522, C/C of rs1642785, and G/G of rs2909430 were associated with an increased incidence of TP53 mutations. Median of overall survival in rs1800372 carriers was comparable to that of patients with TP53 mutations. Other evaluated SNPs were not associated with survival. Conclusion: Our data suggest that some TP53 variants may affect the risk of CLL. rs1800372 polymorphism might be the marker of unfavorable prognosis of the disease.